2006
DOI: 10.1253/circj.70.1200
|View full text |Cite
|
Sign up to set email alerts
|

Nifekalant Hydrochloride Administration During Cardiopulmonary Resuscitation Improves the Transmural Dispersion of Myocardial Repolarization Experimental Study in a Canine Model of Cardiopulmonary Arrest

Abstract: ifekalant hydrochloride (NIF) is the first class III anti-arrhythmic agent for intravenous use covered by National Health Insurance in Japan for refractory ventricular tachycardia and fibrillation (VT/VF). NIF blocks the delayed rectifier K + channels, especially the IKr channels. NIF also has some potential to block the inward rectifier K + current IK1 and transient outward K + channel Ito. Thus it prolongs the action potential duration (APD) and stops VT/VF by extending the refractory period. 1,2 However, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…In-vivo electrophysiology experiments were conducted following open thorax surgery under anesthesia (α-chloralose, 80 mg/kg and urethane, 1000 mg/kg) [10]. An array of 8 × 8 monopolar electrodes (64Map) to cover 7 × 7 mm square (interpolar distance, 1 mm) was put on the LV wall between the left anterior descending branch (LAD) and left circumflex branch (LCx) of coronary arteries (Fig.…”
Section: In-vivo Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…In-vivo electrophysiology experiments were conducted following open thorax surgery under anesthesia (α-chloralose, 80 mg/kg and urethane, 1000 mg/kg) [10]. An array of 8 × 8 monopolar electrodes (64Map) to cover 7 × 7 mm square (interpolar distance, 1 mm) was put on the LV wall between the left anterior descending branch (LAD) and left circumflex branch (LCx) of coronary arteries (Fig.…”
Section: In-vivo Experimentsmentioning
confidence: 99%
“…An array of 8 × 8 monopolar electrodes (64Map) to cover 7 × 7 mm square (interpolar distance, 1 mm) was put on the LV wall between the left anterior descending branch (LAD) and left circumflex branch (LCx) of coronary arteries (Fig. 5A) [10]. The 64Map signals recorded simultaneously were acquired and processed by a computer.…”
Section: In-vivo Experimentsmentioning
confidence: 99%
“…In contrast, the shortening of action potential duration and transmural dispersion are considered to play a role in acute ischemia, and the effect of nifekalant in prolonging the action potential and decreasing transmural dispersion would be more effective in such cases. 16) In the electrocardiographic parameters, the QTc interval was significantly prolonged by nifekelant and the degree of the QTC prolongation was greater in the effective group than in the non-effective group (Figure). That result indicated that the QTc prolongation caused by the nifekalant may vary in individual patients even with the same amount of the drug, and more effective results would be expected in patients with a larger QTc prolongation.…”
Section: Clinical Effects Of Nifekalant and Patient Characteristicsmentioning
confidence: 95%
“…Two prospective randomized studies showed that use of amiodarone improved survival until hospital admission, and amiodarone became a first-line anti-arrhythmic agent for refractory VF/pulseless VT. 23,24 In Japan, nifekalant, another class III anti-arrhythmic agent for refractory VT and VF, has been available since 1999, and some studies have indicated its effectiveness in emergency settings. 25,26 Further studies into what kind of anti-arrhythmic agent would be effective for shock-resistant VF should be undertaken.…”
Section: T His Registry Of Vf At Ccmcs In Osaka Suggestedmentioning
confidence: 99%